Paraquat intoxication. - Serra, Adelaide (2003)
Paraquat, widely used as a contact herbicide is, in some environments (meanly rural), the principal mean of suicide. Commercially known as Gramoxone, it was sintetyzed for the first time in 1882 and its herbicide properties were not discovered until 1955. The authors made a literature review and describe the historic perspective, physicochemical properties, clinic aspects, prognosis factors and treatment and, finally, propose a therapeutic approach having always in mind the capital importance of the early beginning of general treatment of intoxication cases.